Tuning Metamaterials for Applications at DUV Wavelengths - Andrew Estroff; Bruce W. Smith (International Journal of Optics)
The unique properties of metamaterials, namely, their negative refractive index, permittivity, or permeability, have gained much recent attention. Research into these materials has led to the realization of a host of applications that may be useful to enhance optical nanolithography. A selection of materials has been examined both experimentally and theoretically to verify their support of surface plasmons, or lack thereof, in the DUV spectrum via the attenuated total reflection (ATR) method using the Kretschmann configuration. At DUV wavelengths, materials that were previously useful at mid-UV and longer wavelengths no longer act as metamaterials. Structured materials comprised of alternating layers of aluminum and aluminum oxide (Al2O3), as well as some other absorption-free dielectrics, exhibit metamaterial behavior, as do some elemental materials such as aluminum. These elemental and structured materials exhibit the best properties for use in plasmonic nanolithographic applications. Therefore, a simulator was created to examine material and thickness combinations to generate a tunable metamaterial for use in the DUV. A method for performing plasmonic interference lithography with this metamaterial has been proposed, with calculations showing the potential for half-pitch imaging resolution of 25 nm.